Keterbukaan Dan Akuntabilitas Dalam Penyelenggaraan Pemerintahan Desa Lermatang Kecamatan Tanimbar Selatan Kabupaten Kepulauan Tanimbar - Bulohroy, Flora Tiabetris Celsa; Mustamu, Julista; Pattinasarany, Yohanes (Jurnal Saniri, 2023)
Introduction: Openness and Accountability are principles in the administration of government, including in the administration of village government, so that every government administrator, including the village government of Lermatang, South Tanimbar sub-district, Keulauan Tanimbar Regency, is obliged to apply the principles of openness and accountability in the process of Government Administration, Village Development, Community Development and Community Empowerment. In the explanation of Article 24 letter d of Law no. 6 of 2014 that Openness is a principle that opens itself to the right of the community to obtain correct, honest, and non-discriminatory information regarding the Implementation of Village Government by taking into account the provisions of the legislation. While accountability according to the explanation of Article 24 letter g of Law no. 6 of 2014 is the principle that determines that every activity and the final result of the implementation of Village Government activities must be accountable to the Village community in accordance with the provisions of the legislation. In the administration of village government, the village government as the organizer of the village government in carrying out the tasks and authorities given must be open and responsible for the actions or actions taken. However, the facts found are that the Lematang Village Government does not comply with the rules as mentioned above, and/or does not apply the Principles/Principles of Openness and Accountability in the Village Administration process.Purposes of the Research: To research and analyze the Implementation of Government in Lematang Village, South Tanimbar Tanimbar, Tanimbar Islands Regency, it is carried out in an open and accountable manner and the legal consequences for the Government in Lermatang Village, South Tanimbar District, Tanimbar Islands Regency if it is not open and accountable in the administration of government.Methods of the Research: The method used is a normative juridical research method using descriptive analysis of legal materialsResults of the Research:  The results of the study indicate that in the administration of government in the village of Lematang, South Tanimbar District, Tanimbar Regency, the Lematang village government does not apply openness and accountability in carrying out all government affairs that are under the authority of the village. Therefore, the legal consequence for the Lematang village government if it is not open and accountable in the administration of village government is that it should be subject to administrative sanctions (dismissal) from position as village head.